Distribution Transformer Synchronization Simulation with Two Different Vector Groups using the Matlab Simulink - Brainvendra Widi Dionova; Taopik Hidayat; Sinka Wilyanti; M. N. Mohammed (Jurusan Teknik Elektro Universitas Andalas, 2022)
Nowadays, the quality of electrical energy really needs to be improved especially for industrial purposes that require a good level of reliability in the distribution of electrical energy. Maintenance of distribution transformers is routinely carried out to ensure that the quality of electrical energy produced is in accordance with standards. This maintenance is done using the customer’s load from the distribution transformer to the mobile substation transformer, that can be done using synchronization. This synchronization requires the same distribution transformer vector groups, otherwise it will produce non-standard output. The aim of this research is to determine the vector groups effect on parallel transformer installation system, the method to overcome the synchronous problem of different vector groups based on simulating and testing the synchronization of a 20 / 0.4 kV distribution transformer with the Dyn5 and Dyn11 vector groups. The results obtained from this research are two transformers that have different vector groups can be synchronized with an abnormal connection (changing the position of the secondary terminal cable connection and the primary terminal cable) so that it will produce the same voltage phase. This will abnormal treatment of distribution transformers maintenance that do not have a back-up transformer with the same vector group still can use the different vector group transformers.